Assessment of language policy of the people of Kazakhstan: results of a sociological study (Хабаршы. Психология және социология сериясы, 2025)
This article presents the results of sociological analysis of the population's assessment of the language policy in the Republic of Kazakhstan. The main purpose of the research is to study the opinions of different social categories of Kazakhstani people on the issues of language policy conducted in the country. The results of the sociological survey conducted by the Language Policy Committee of the Ministry of Science and Higher Education of the Republic of Kazakhstan (for 2021-2023) were the theoretical basis for this study.The study analyzed the initial data using the qualitative method of Desk Research, the application of which, in turn, confirms the scientific and practical significance of the article.As a result of the analysis, a number of differences were noted, giving the study a gendered perspective. The problems identified as a result of the study require further analysis, which increases the need to conduct an observation of the dynamics of the indicators identified during the writing of the article, which makes a certain contribution to scientific research in the field of sociolinguistics. The conclusions formulated in the course of the study make it possible to determine those optimal methods that will contribute to improving the effectiveness of language policy implementation in the country. In this respect, this article, its scientific results, can serve as a basis for the continuation of scientific analysis of this problem.Keywords: language policy, Kazakh language, Kazakhstanis, social groups, sociology.